Spatial and temporal variability of temperature, precipitation, and solar radiation in Magdalena department, Colombia from 2000 to 2022 - Aldair Valle-Garcia; Sheimy Lozano-Bustamante; Yiniva Camargo-Caicedo (Heliyon)
Climate variability analysis is crucial for understanding current patterns and predicting future climate behavior. This knowledge is essential for decision-making about mitigation and reduction activities to combat climate change from those activities that may cause abrupt changes in climate dynamics. The present study analyzed climate variability in the Magdalena department, Colombia, over a 22-year period. Temperature, solar radiation, and precipitation data from NASA's Giovanni reanalysis and simulation are used with data from local meteorological stations. Statistical homogeneity and trend tests were applied to find climate patterns using RStudio software. The results showed that the years 2010 and 2011 were the wettest in the time series. Conversely, 2015 was the warmest year on record in the time series. This analysis provides a more comprehensive understanding of the climate variability in the region, laying the foundation for future studies on this subject.